Tranexamic Acid in Combination With Vancomycin or Gentamicin Has a Synergistic Effect Against Staphylococci - Benjumea, Antonio; Díaz-Navarro, Marta; Hafian, Rama; Cercenado, Emilia; Sánchez-Somolinos, Mar; Vaquero, Javier; Chana, Francisco; Muñoz, Patricia; Guembe, María (Frontiers in Microbiology, 2022)
Background Tranexamic acid (TXA) is an antifibrinolytic agent applied in orthopedic surgery and has been proven to reduce post-surgery infection rates. We previously showed that TXA also had an additional direct antimicrobial effect against planktonic bacteria. Therefore, we aimed to evaluate whether it has a synergistic effect if in combination with antibiotics. Materials and Methods Three ATCC and seven clinical strains of staphylococci were tested against serial dilutions of vancomycin and gentamicin alone and in combination with TXA at 10 and 50 mg/ml. The standardized microtiter plate method was used. Minimal inhibitory concentrations (MICs) were calculated by standard visualization of well turbidity (the lowest concentration at which complete absence of well bacterial growth was observed by the researcher) and using the automated method (the lowest concentration at which ≥80% reduction in well bacterial growth was measured using a spectrophotometer). Results Tranexamic acid-10 mg/ml reduced the MIC of vancomycin and gentamicin with both the standard method (V: 1-fold dilution, G: 4-fold dilutions) and the automated turbidity method (vancomycin: 8-fold dilutions, gentamicin: 8-fold dilutions). TXA-50 mg/ml reduced the MIC of gentamicin with both the standard turbidity method (6-fold dilutions) and the automated turbidity method (1-fold dilutions). In contrast, for vancomycin, the MIC remained the same using the standard method, and only a 1-fold dilution was reduced using the automated method. Conclusion Ours was a proof-of-concept study in which we suggest that TXA may have a synergistic effect when combined with both vancomycin and gentamicin, especially at 10 mg/ml, which is the concentration generally used in clinical practice.